2014
DOI: 10.1080/1539445x.2014.937495
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Dynamics in a Polymer-Solid Interphase: Molecular Dynamics Simulations of 1,4-Polybutadiene At a Graphite Surface

Abstract: A chemically realistic model of 1,4-polybutadiene confined by graphite walls in a thin film geometry was studied by molecular dynamics simulations. The chemically realistic approach allows for a quantitative determination of a variety of experimentally accessible relaxation functions (e.g., dielectric, NMR, or neutron scattering responses). The simulations yield these experimental observables. Additionally, the simulations can be resolved as a function of distance to the solid interface on a much finer scale t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 46 publications
(57 reference statements)
1
24
0
Order By: Relevance
“…The latter was attributed to hydrogen bonding at the interface that restricted the polymer mobility. Since then, several experimental and theoretical studies reported the effect of confinement on segmental mobility for polymer films, , sometimes, however, with conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…The latter was attributed to hydrogen bonding at the interface that restricted the polymer mobility. Since then, several experimental and theoretical studies reported the effect of confinement on segmental mobility for polymer films, , sometimes, however, with conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…The increase can be significant over a length up to a few tens of nanometer. This phenomenon is of crucial importance in filled polymerssuch as car tiressince the confined polymeric zones between fillers have been shown to control most of the mechanical properties of the macroscopic samples [24]. In most filled polymers, a slight shift of the macroscopic glass transition temperature is observed, of the order of a few Kelvins.…”
mentioning
confidence: 99%
“…This technique captures the chemical details and, thus, describes chemistry-specific polymer–solid interactions. Polymer/graphene or polymer/graphite hybrid materials can serve as a good example of hybrid materials containing flat surfaces [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. In these studies, the properties are analyzed as a function of the distance from the flat surface, quantifying in such a way the extension of the interphase region, i.e., extension of the region of the altered properties with respect to expected bulk-like behavior of the given polymer.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the properties are analyzed as a function of the distance from the flat surface, quantifying in such a way the extension of the interphase region, i.e., extension of the region of the altered properties with respect to expected bulk-like behavior of the given polymer. Solar et al in a series of studies investigated the polybutadiene (PB) films confined by graphite [ 38 , 39 , 40 ] in which they attributed the dynamical changes near the surface to the interplay of the local density changes near the wall (i.e., enhanced packing near the surface) with the rotational barriers. Pandey et al [ 34 ] performed a detailed spatio-temporal analysis of polyisoprene (PI) on graphite and linked the particular conformation of the adsorbed chain (i.e., train, loop or tail) with its segmental dynamics and its position relative to the surface.…”
Section: Introductionmentioning
confidence: 99%